2022
DOI: 10.1101/2022.07.23.22277950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating Isoniazid Preventive Therapy into the Fast-Track HIV Treatment Model in Urban Zambia: A Proof-of -Concept Pilot Project

Abstract: IntroductionMost people living with HIV (PLHIV) who are established on treatment in Zambia receive multi-month prescribing and dispensing (MMSD) of antiretroviral therapy (ART) and are enrolled in less-intensive differentiated service delivery (DSD) models, such as Fast Track (FT), in which clients pick up ART every 3-6 months and make clinical visits to health facilities every 6 months. In 2019, Zambia introduced Isoniazid Preventive Therapy (IPT) with scheduled visits at 2 weeks and 1, 3, and 6 months. The a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…Unlike our study, two systematic reviews of latent tuberculosis cascade-of-care among PLHIV found very low completion rates as low as 33.2% [ 18 ] and 18.8% [ 19 ], which were much lower than we found in our study. The higher IPT completion found in our study compared to the above two systematic reviews is an indicator of the high quality of the IPT program in Uganda [ 20 ], which followed the implementation of IPT Surge activities by the Uganda Ministry of Health with technical and financial support from development partners.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike our study, two systematic reviews of latent tuberculosis cascade-of-care among PLHIV found very low completion rates as low as 33.2% [ 18 ] and 18.8% [ 19 ], which were much lower than we found in our study. The higher IPT completion found in our study compared to the above two systematic reviews is an indicator of the high quality of the IPT program in Uganda [ 20 ], which followed the implementation of IPT Surge activities by the Uganda Ministry of Health with technical and financial support from development partners.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings align with other studies, including one in urban Zambia designed to integrate 6 months of IPT into a Fast Track model, using monthly phone appointments with community healthcare workers (CHWs) who provided adherence counselling and monitored side effects [ 25 ]. TPT completion rates in this project were high (90.2%) although only 65.9% of clients participated in all phone appointments.…”
Section: Discussionsupporting
confidence: 84%
“…Another study in Pakistan integrated 3HP into prison systems and adverse events resulted in 8.6% of participants discontinuing 3HP [ 29 ]. In the Uganda study, 36% of those who completed IPT reported one or more side effects [ 13 ], while 8.1% of clients enrolled in the TPT study in Zambia reported side effects to CHWs during phone check‐ins [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation